2022
DOI: 10.3390/nano12132280
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodispersed Titanium Nitride Quantum Dots for Harmonic Mode-Locking Generation in an Ultrafast Fiber Laser

Abstract: As a member of the transition metal nitride material family, titanium nitride (TiN) quantum dots (QDs) have attracted great attention in optical and electronic fields because of their excellent optoelectronic properties and favorable stability. Herein, TiN QDs were synthesized and served as a saturable absorber (SA) for an ultrafast fiber laser. Due to the strong nonlinear optical absorption characteristics with a modulation depth of ~33%, the typical fundamental mode-locked pulses and harmonics mode-locked pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In addition, the performances of the proposed SA and SESAM [ 49 ] as well as those of various reported typical 2D SA‐based (including graphene, [ 50 ] carbon nanotubes, [ 51 ] gold nanowires, [ 52 ] TIs, [ 53,54 ] transition metal dichalcogenides (TMDs), [ 55–58 ] Metal–organic frameworks (MOFs), [ 59 ] ferromagnetic insulators, [ 60 ] BP, [ 61 ] MXenes, [ 62 ] bismuthine, [ 63 ] tellurene, [ 64 ] and antimonene [ 65 ] ) passive mode‐locking fiber lasers are summarized in Table 1 . The HML based on the 2D MoSe 2 SA exhibited the highest repetition rate (3.27 GHz); however, the modulation depth and saturable intensity were both low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the performances of the proposed SA and SESAM [ 49 ] as well as those of various reported typical 2D SA‐based (including graphene, [ 50 ] carbon nanotubes, [ 51 ] gold nanowires, [ 52 ] TIs, [ 53,54 ] transition metal dichalcogenides (TMDs), [ 55–58 ] Metal–organic frameworks (MOFs), [ 59 ] ferromagnetic insulators, [ 60 ] BP, [ 61 ] MXenes, [ 62 ] bismuthine, [ 63 ] tellurene, [ 64 ] and antimonene [ 65 ] ) passive mode‐locking fiber lasers are summarized in Table 1 . The HML based on the 2D MoSe 2 SA exhibited the highest repetition rate (3.27 GHz); however, the modulation depth and saturable intensity were both low.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the output harmonic pulses exhibited a higher repetition rate and excellent SNR under moderate pump power levels, which is preferable for engineering applications, including ultrahigh-speed optical time-division multiplexing systems, [46] ultrafast all-optical sampling, [47] and all-optical clock recovery. [48] In addition, the performances of the proposed SA and SESAM [49] as well as those of various reported typical 2D SA-based (including graphene, [50] carbon nanotubes, [51] gold nanowires, [52] TIs, [53,54] transition metal dichalcogenides (TMDs), [55][56][57][58] Metal-organic frameworks (MOFs), [59] ferromagnetic insulators, [60] BP, [61] MXenes, [62] bismuthine, [63] tellurene, [64] and antimonene [65] ) passive mode-locking fiber lasers are summarized in Table 1. The HML based on the 2D MoSe 2 SA exhibited the highest repetition rate (3.27 GHz); however, the modulation depth and saturable intensity were both low.…”
Section: Harmonic Mode Lockingmentioning
confidence: 99%
“…There are reports about the plasmonic metal nitrides and phosphides such as TiN, 364–366 InN, 367 and Cu 3− x P nanostructured materials 368 as the SAs for applications in passively mode-locked fiber lasers. For instance, Xian et al reported the passively mode-locked fiber laser centered at 1562 nm with pulsed duration down to 763 fs in EDFL by using the TiN nanoparticles as the SA in 2019 (Fig.…”
Section: Applications Of Emerging Nanostructured Materials As the Sas...mentioning
confidence: 99%
“…As a kind of non-noble metal material, TMNs exhibit similar surface and adsorption properties to the VIII group of precious metals (such as Pt and Pd) because the atomic distance between metal atoms increases and the d-band center downshifts after the incorporation of nitrogen atoms [ 21 , 22 ]. Combined with attractive electrical conductivity, robust chemical stability, and remarkable mechanical robustness, TMNs have great potential as high-efficiency catalysts in various areas such as electrocatalysis, hydrogenation/desulfurization of fuel oil, synthesis/decomposition of ammonia, and other fields [ 23 , 24 , 25 , 26 ]. Moreover, their impressive chemical inertness and high corrosion resistance allow TMNs to be applied in a wide array of pH conditions for long periods, expanding the electrocatalytic application in various mediums [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%